Glaucoma and Antioxidants: Review and Update - Jose Javier Garcia-Medina; Elena Rubio-Velazquez; Maria Dolores Lopez-Bernal; Alejandro Cobo-Martinez; Vicente Zanon-Moreno; Maria Dolores Pinazo-Duran; Monica del- (MDPI AG, 2020)
Glaucoma is a neurodegenerative disease characterised by the progressive degeneration of retinal ganglion cells. Oxidative stress has been related to the cell death in this disease. Theoretically, this deleterious consequence can be reduced by antioxidants substances. The aim of this review is to assemble the studies published in relation to antioxidant supplementation and its effects on glaucoma and to offer the reader an update on this field. With this purpose, we have included studies in animal models of glaucoma and clinical trials. Although there are variable results, supplementation with antioxidants in glaucoma may be a promising therapy in glaucoma.